Comparative study of Ringer’s lactate solution and 6% hydroxyethyl starch solution as pre-loading fluid for prevention of hypotension following spinal anesthesia - Singh, T. Mohan; Linus, Lesley (International Journal of Research in Medical Sciences, 2017)
Background: Arterial hypotension following spinal anesthesia still remains the leading cause for maternal mortality and morbidity. Active management of hypotension and more so its prevention of its ads more safety value to spinal anesthesia, which is widely practiced worldwide. Preloading of patients with either crystalloid or colloid prevents the severity of hypotension. Objectives of the study was to compare the preloading efficacy of Ringers lactate solution (20 ml/kg) and 6% hydroxyl ethyl starch at 10 ml/kg in prevention of hypotension following spinal anesthesia in elective caesarean section. Methods: 100 ASA grade I and grade II subjects for elective caesarean section were studied in two groups. Group A (Ringer lactate group) 50 subjects and Group B (hydroxyl ethyl starch group) 50 subjects. Each group was preloaded over a period of 20 minutes before spinal anesthesia with either ringer lactate solution (Group A) at 20 ml/kg or 6% hydroxyl ethyl starch group at 10 ml/kg body weight. Main outcome measures were mean systolic blood pressure, mean diastolic blood pressure, mean arterial blood pressure and mean heart rate. Results: Demographic characteristics of both groups were comparable. Incidence of hypotension was significantly more in ringer lactate group. There was no significant difference of heart rate in both the groups. No allergic reaction was noted to hydroxyl ethyl starch. Vasopressor requirement was also low in hydroxyl ethyl starch group compared to ringer lactate group. Conclusions: Preloading subjects with 6% hydroxyl ethyl starch is beneficial than preloading with ringer lactate solution as it produces better hemodynamic stability to subjects.